Buxus Microphylla var. Koreana Nakai Extract for the Treatment of Gastric Cancer - Lee Hee Jung; Kim Min Chul; Lim Bora; Kim Byung Joo (Korean Pharmacopuncture Institute, 2013)
Objectives: Buxus Microphylla var. Koreana Nakai Extract (BMKNE) is used as a folk remedy for malaria and veneral disease. In the present study, we investigated the effects of BMKNE in the growth and the survival of AGS cells, the most common human gastric adenocarcinoma cell lines. Methods: The AGS cells were treated with varying concentrations of BMKNE. Analyses of the sub G1 peak, the caspase-3 and -9 activities, and the mitochondrial depolarization were conducted to determine whether AGS cell death occured by apoptosis. Also, to identify the role of transient receptor potential melastatin (TRPM) 7 channels in AGS cell growth and survival, we used human embryonic kidney (HEK) 293 cells overexpressed with TRPM7 channels. Results: Experimental results showed that the sub G1 peak, the caspase-3 and -9 activities, and the mitochondrial depolarization were increased. Therefore, BMKNE was found to induce the apoptosis of these cells, and this apoptosis was inhibited by SB203580 (a p38 mitogen-activated protein kinase (MAPK) inhibitor), and by a c-jun NH2-terminal kinase (JNK) II inhibitor. Furthermore, BMKNE inhibited TRPM7 currents and TRPM7 channel over-expressions in HEK 293 cells, exacerbating BMKNE-induced cell death. Conclusions: These findings indicate that BMKNE inhibits the growth and the survival of gastric cancer cells due to a blockade of the TRPM7 channel's activity and MAPK signaling. Therefore, BMKNE is a potential drug for treatment of gastric cancer, and both the TRPM7 channel and MAPK signaling may play an important role in survival in gastric cancer cells.